POTS and Antiphospholipid Syndrome: An Unlikely Association - Zee, Kalvin; Qureshi, Shakaib (Case Reports in Rheumatology, 2021)
Antiphospholipid syndrome is a rare complication of postural orthostatic tachycardia syndrome. Clinically, the presentation has overlapping symptoms of both diseases, with lightheadedness or syncope when moving from a supine to a standing position as well as blood clots, headache, or pregnancy complications in women. This case presentation involves a 39-year-old patient identified as female who has been diagnosed with POTS and elevated anticardiolipin antibodies.